When patients die: patient memorials and group reflection in an internal medicine residency program. Issue 1 (2nd January 2021) - Oakman, Nicole; Lim, Jonathan; Bui, Christine; Kaplan, Holland; Sherman, Stephanie
Abstract: Patient death is a formative and emotional experience for physicians. Medical trainees are particularly susceptible to the emotional impact of patient death. However, few studies have examined how trainees process patient death. This study describes annual patient memorials organized at a large multisite academic graduate medical education program. Peer-led, 1-hour patient memorial services were organized for internal medicine residents, including large and small group reflection, a moment of silence, and collective art projects. At the conclusion of each memorial, participants completed a 10-question survey regarding their experience during the memorial and their prior experiences with patient death. Ninety-nine surveys were analyzed over 2 years. Of resident respondents, 84% reported feeling comfortable or very comfortable participating in the memorials, and 93% rated reflection on patient death as important or very important. When asked how they reflect on patient death, 67% of residents reported processing patient death independently, while only 23% reported processing patient death with their medical teams. Patient memorials with small and large group discussions are easily adopted and replicated. Residents reflect on patient death frequently but often independently rather than with their medical teams. Patient memorials provide a venue for collective mourning and group reflection to support trainees.